Analysis for Fire Plume Temperature in Developing Area and Radiation Heat Flux Distribution in Small-scale Pool Fire. (2018) - Shen, Gan-su; Jiang, Jun-cheng; Zhou, Kui-bin; Zhang, Shao-jie; Wu, Fan; Zou, Meng-ya
Abstract: Pool fires are the most common burning phenomena that are often reported to cause huge casualties and properties in process industry accidents. Therefore, it is important to deeply understand the combustion characteristic and thermal radiation of pool fires. This paper presents experimental study and theoretical analysis on the fire plume temperature in developing area and thermal radiation distribution of small-scale propane pool fires. The results show that fire plume temperature should be formulated by ( z/Q 2/5 ) for z/Q 2/5 ranging from 0 to 0.02, in comparison with the constant temperature assumption in literature. The fire plume temperature reaches the maximum value as z/Q 2/5 equals 0.02. The Point Source Model and Shokri-Beyler Correlation can relatively accurately calculate the radiant heat flux, while Mudan-Croce Method gives a bad prediction on the thermal radiation in small pool fires.